Anticipation and Solutions for Cost Overruns of Material Costs in Toll Road Construction Projects - Isfahani, Muhammad Nafhan; Antonius, Antonius; Wibowo, Kartono (Universitas Ibn Khaldun Bogor, 2025)
This paper presents the results of research on anticipation and solutions for material cost overrun in the open system Toll Road project in Jadebotabek. The purpose of this study is to determine the anticipation and solutions for handling material cost overrun. This study was conducted by surveying 76 correspondents consisting of Managers, Consultants and Contractors involved in the construction of Toll roads in Jadebotabek. The survey results were tested for validity and reliability to determine the dominant factors causing cost overrun, then the development of anticipation and solutions for handling material cost overrun was carried out by a team of experts. The results of the study showed that there were 10 valid factors causing cost overrun with a coefficient value of 0.389 - 0.716 and 13 reliable factors causing cost overrun with a Cronbach's alpha value above 0.700. The results of this study also show that anticipation and solutions for handling material cost overrun in toll road projects are preventive measures to reduce and eliminate the occurrence of cost overrun at the planning stage and at the implementation stage.